Les Guilhem de Montpellier et leur entourage urbain (1090-1204) : les apports de l’approche prosopographique - Alexandre Vergos (Les Cahiers de Framespa)
The Guilhem family, lords of Montpellier, were one of the great feudal families of Languedoc in the 12th century. Relying on the wealth of Montpellier, a new town in full expansion, they imposed their authority on the surrounding castellans and destabilised the power of the Count of Melgueil, their suzerain. The drastic change in the composition of the Guilhem entourage over the course of the century reflects the transformation of power relations within a flourishing merchant town. This article examines the growing importance of bourgeois in a seigniorial entourage and, more specifically, the way in which the Guilhems integrated them into their strategies to perpetuate their seigniory and strengthen their regional alliances. This prosopographical study is based on a database that integrates all the preserved acts of this dynasty and lists all the active participants in this period.